Prevalência de anemia nas gestantes atendidas em unidades de saúde da família em Feira de Santana, Bahia, entre outubro de 2005 e março de 2006. - Santos, Pedro Nascimento Prates (2006)
Introduction: Nutritional deficiencies and consequent anemia constitute important Public Health problems. Health initiatives and public policies, with the object of preventing and treating these problemsf have increasingly been developed jn the last two decades (WHO; UNCF; UNU, 2001 ). Anemia is a disorder characterized by a reduction in the concentration of hemoglobin compared to reference levels. During pregnancy iron deficiency can be associated with multiple problems for both the mother and fetusf including heightened risk of hemorrhagef sepsisf maternal mortalityf perinatal mortality and low birth weight (WHO; UNCF; UNUf 2001). General objectives: To estimate the prevalence of anemia in pregnant women attended by the Family Health Care Units (USF) in the municipality of Feira de Santana within the period between october 2005 and March 2006. Specifc objetctives: To characterize the sociodemographicf socioeconomc and gynecological-obstetrical factors associated with the development of anemia in the pregnant women; to classify morphologically, and by severity, the anemia affecting the study population; to support pre-natal health initiatives for the treatment and, above all else, the prevention of this ailment. Methodology: A descriptive prevalence study was undertaken, seeking associations between possible correlated factors. The research included a representative study group of pregnant women attended by the Family Health Care Units in the municipality of Feira de Santana within the period between October 2005 and March 2006. A questionnaire containing question blocks related to personal details (age, weight, height, skin color), sociodemographic and socioeconomic information (including, amongst other questionsf marital status, education and salary), gynecologic and obstetric history (menarche, number of pregnancies, interval between pregnancies ant1 the use of anti-anemic drugs). Hematologic results (hemoglobin and hematocrit) were obtained from a testing laboratory that provides services to the Brazilian Health System (SUS) in Feira de Santana and attends to, amongst others, the pregnant women assisted by the USF . Results: The descriptive analysis showed that 31,9% of pregnant women interviewed were anemic. Through exploratory analysis the association between the occurrence of anemia and sociodemografic arid socioeconomic (low education levels, low family income and unstable living conditions), gynecological and obstetrical (pregnancy trimester, previous abortions, low birth weight in previous pregnancies) factors became evident. The analysis of the relationship between the occurrence of anemia in the women and anthropometric data revealed a connection with low birth weight. Conclusion: The results obtained point to the need to intervence in order to minimilize the causes of anemia, with the objective of reducing the frequency of this injury in the general population.